2022
DOI: 10.1186/s13102-022-00541-y
|View full text |Cite
|
Sign up to set email alerts
|

Classified metabolic power-based measures in professional football players: comparison between playing positions and match period

Abstract: Objective The aim of this study was (i) provide reference data of metabolic power-based measures during professional football matches; and to (ii) analyze the between-position and between-halves differences of power-based measures during professional football matches. Methods Forty-six professional male players from two Turkish Super League teams were observed during two seasons, and 58 matches were analyzed. Total distance, equivalent distance, Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Analyzing the differences among roles, when significant differences were detected, MF often presented higher levels of AP and PEm at different intervals compared to one or more playing positions. Although Hoppe [19] and Guerrero-Calderón [20] have not found any differences between roles AP, our results are in agreement with different studies [1,21], confirming that MFs exerted more AP in different time played than other roles.…”
Section: Role Differencessupporting
confidence: 90%
See 1 more Smart Citation
“…Analyzing the differences among roles, when significant differences were detected, MF often presented higher levels of AP and PEm at different intervals compared to one or more playing positions. Although Hoppe [19] and Guerrero-Calderón [20] have not found any differences between roles AP, our results are in agreement with different studies [1,21], confirming that MFs exerted more AP in different time played than other roles.…”
Section: Role Differencessupporting
confidence: 90%
“…The execution of soccer-related movements imposes large physiological loads on players during competition. Studies have shown that activity profile is role-positioning dependent [1][2][3][4][5] and that locomotor activity, such as high-intensity running, is affected by the time played [5]. Despite a low average match speed (110-140 m • min-1, in a 90-minute game) [4], soccer players may experience remarkable neuromuscular fatigue and energy expenditure during the game [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on elite football players, both senior and youth, has observed signs of fatigue such as a decrease in metabolic power [24] and a decline in the ability to accelerate and decelerate as the match progresses, varying by player position [1,2,6,24,25]. Most of these studies point to a decline in the second half of matches, especially greater in the last 20' of play [2,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…After an initial increase at the beginning of the second half, the trend declines steadily [2,10], but there is disagreement on quantifying these variables during a match. Some studies examine changes every 15' [1,24,26,27,29,30], while others prefer 10' [14] or 5' intervals [10,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation